Lost therapeutic potential of monocyte‐derived dendritic cells through lost tissue homing: stable restoration of gut specificity with retinoic acid. (8th September 2013) - Bernardo, D.; Mann, E. R.; Al‐Hassi, H. O.; English, N. R.; Man, R.; Lee, G. H.; Ronde, E.; Landy, J.; Peake, S. T. C.; Hart, A. L.; Knight, S. C.
Summary: Human monocyte‐derived dendritic cells (DC) (MoDC) are utilized for immunotherapy. However, in‐vitro immunological effects are often not mirrored in vivo . We studied the tissue‐homing potential of MoDC. Circulating monocytes and DC expressed different tissue‐homing markers and, during in‐vitro development of MoDC, homing marker expression was lost resulting in a 'homeless' phenotype. Retinoic acid (RA) induced gut‐homing markers (β7 and CCR9) and a regulatory phenotype and function [decreased human leucocyte antigen D‐related (HLA‐DR) and increased ILT3 and fluorescein isothiocyanate (FITC‐dextran uptake) in MoDC]. RA‐MoDC were less stimulatory and primed conditioned T cells with a gut‐homing profile (β7 + CLA − ). Unlike the normal intestinal microenvironment, that from inflamed colon of ulcerative colitis (UC) patients did not induce regulatory properties in MoDC. However, RA‐MoDC maintained their regulatory gut‐specific properties even in the presence of UC microenvironment. Therefore, MoDC may be ineffectual for immunotherapy because they lack tissue‐homing and tissue‐imprinting specificity. However, MoDC rehabilitation with gut‐homing potential by RA could be useful in promoting immunotherapy in pathologies such as UC.